Β-Cyclodextrin-based supramolecular nanoparticles: pH-sensitive nanocarriers for the sustained release of anti-tumor drugs. (4th November 2022) - Li, Bi-Lian; Wang, Chun-Lei; Wang, Qin; Yang, Jian-Mei; Chi, Shao-Ming; Chen, Jian-Chong; Zhang, Jin; Zhao, Yan
Abstract : CSL-loaded SBE7 -β-CD/HDBAC nanoparticles present pH-trigger controlled release properties, which may enhence the therapeutic effects of the anti-tumor compound CSL. Abstract : Chemotherapy is one of the effective ways to treat cancer because of its ability to control lesions quickly. However, chemotherapy can have many side effects due to chemotherapy indiscriminately killing cancer cells and normal cells. Targeted chemotherapy strategies may be able to improve this problem effectively. In this work, pH-responsive nanoparticles based on sulfobutyl ether-β-CD (SBE7 -β-CD) and cetylbenzyldimethylammonium chloride (HDBAC) were designed and prepared. The obtained nanoparticles showed assembly and disassembly behaviors with the pH alternating between 10.0 and 2.0, and were adopted to encapsulate and release the anti-tumor drug celastrol (CSL). Moreover, CSL-loaded nanoparticles exhibited sustained release action for 82 h, which suggests that it may show potential in improving the therapeutic effects. In cell experiments, CSL-loaded nanoparticles displayed fewer cytotoxic effects on healthy cells, while significant cytotoxicity on five human cancer cells. Notably, CSL-loaded nanoparticles showed a higher apoptosis rate on liver cancer SMMC-7721cells than free CSL. We hope that the nanoparticles can be clinically used as sustained-release carriers for anticancer drugs after further research.